2011
DOI: 10.3109/17477161003728469
|View full text |Cite
|
Sign up to set email alerts
|

Assessing dietary intake in children and adolescents: Considerations and recommendations for obesity research

Abstract: Dietary intake and food habits are important contributors to the obesity epidemic. They are highly modifiable components of energy balance and are usually targeted in both obesity prevention and treatment programs. However, measurement of total diet creates challenges and can convey a large burden in terms of cost, technical expertise, impact on respondents and time. It is not surprising therefore that comprehensive reports of dietary intake in children are uncommon and, when reported, have limitations. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
158
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(162 citation statements)
references
References 47 publications
1
158
1
2
Order By: Relevance
“…Finally, the BMI-for-age z scores suggested that the children were, on average, heavier than the American reference population, one of the many variables known to be associated with underreporting. [34][35][36][37] Against the backdrop of limited testeretest reliability of the modified MEDFICTS in the group as a whole and specifically among boys the lack of significant correlations between the final score in the modified MEDFICTS and the PFE, PSFE, and cholesterol in the food records was not surprising. Thus, only for girls could a meaningful relative validity be reasonably expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the BMI-for-age z scores suggested that the children were, on average, heavier than the American reference population, one of the many variables known to be associated with underreporting. [34][35][36][37] Against the backdrop of limited testeretest reliability of the modified MEDFICTS in the group as a whole and specifically among boys the lack of significant correlations between the final score in the modified MEDFICTS and the PFE, PSFE, and cholesterol in the food records was not surprising. Thus, only for girls could a meaningful relative validity be reasonably expected.…”
Section: Discussionmentioning
confidence: 99%
“…28,35 Dietary assessment is critical yet remains challenging, particularly amongst children, where cognitive factorsspecifically to record, remember, or generalize intake-as well as restricted knowledge of food and food preparation, limited motivation, and attention span are well-documented child-specific respondent factors that can contribute to error. 27,28,37 True inter-and intraindividual variability are also important. In 5-to 17-year-old children the ratio of intra-to intersubject variances in intake was about twice that observed in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the measurement errors of FR and FFQ are fairly independent, and we considered the estimated FR to be the best alternative when choosing between different dietary assessment methods (6) . The FR method has other limitations however, for example a likely change of dietary habits (38) . Under optimal research conditions, inclusion of an objective measure (e.g.…”
Section: Tablementioning
confidence: 99%
“…In this respect, it should be noted that the questionnaire was administered to caretakers in the presence of the children, thus allowing them to complement the information. 30 Another limitation refers to the fact that estimated DI does not include the energy and nutrients consumed from food complements/ supplements, as reported by 8.3 to 16.7% of subjects. Thus, the nutrient intake of this proportion of subjects may be underestimated to a certain degree.…”
Section: Discussionmentioning
confidence: 99%